Development of in vitro screening approaches to optimise formulation performance. - Gallas, Andrzej (2014)
The pharmaceutical industry has been criticised for a lack of innovation associated with the drug discovery and development process, for example when compared with the computer or music industries. In fact, bringing a new medicine to the market requires, on average, the screening of up to 10 000 molecules, an expense in the range of $500 million-$2 billion and roughly 10-15 years of research. Such a situation not only has a direct impact on the health and life expectancy of every single human being on the planet, but also indicates that alternative strategies for drug development should be investigated. In this thesis, studies of direct formulation-membrane interactions, both in a high throughput (HT) manner and at a nanometre scale, were initially identified as an important approach that could offer advantages for in vitro-in vivo correlations of in-man drug behaviours. Subsequently, supported lipid bilayers (SLBs) of physiologically-relevant lipid compositions were indicated as experimental models of preference for pre-clinical drug development. For that reason, the characterisation and assessment of physicochemical and behavioural properties of the model SLBs at a nanometre scale, as well as development of an SLB microarray for HT applications were the focus of this research. Here, the optimisation and characterisation of model lipid films was performed using atomic force microscopy (AFM), time-of-flight secondary ion mass spectrometry (ToF-SIMS) and X-ray photoelectron spectroscopy (XPS). Additionally, the AFM-investigated assessment of the interactions between model SLBs and formulation components (e.g. Pluronics®, siRNA, DNA polyplexes) enabled both the correlation of in vitro observations with literature-reported in vivo performances of the components of interest and the development of hypotheses with regards a number of phenomena in biology. Furthermore, the development of a SLB microarray prototype suitable for HT applications is reported. Directly, this research improves: the understanding of SLB behaviours and experimental investigation at a nanometre scale of the mechanisms of interactions between membranes and: Pluronics®, nucleic acids and their complexes, as well as the technology of SLB microarray development. Indirectly, this research contributes towards the progress in a number of research areas within pharmaceutical sciences, potentially resulting in new scientific disciplines, such as immunolipidomics or nanopharmacology.